819 A RARE CASE OF RESPIRATORY SENSE LEAD DYSFUNCTION IN A PATIENT WITH A HYPOGLOSSAL NERVE STIMULATOR. (3rd May 2021) - Toolsie, Omesh; Zacharias, Rajesh; Oster, Joel; Ostrow, Peter; Schumaker, Greg; Wein, Richard; Grover, Aarti
Abstract: Introduction: In patients with moderate to severe obstructive sleep apnea (OSA) who are intolerant to PAP therapy, hypoglossal nerve stimulation (HGNS) is being increasingly considered as alternative treatment. Implantation involves placing cuff electrodes on inclusion branches of the hypoglossal nerve and a respiratory effort-sensing lead which is placed between the right intercostal muscle layers. These are connected to the implantable pulse generator which usually sits in a right infraclavicular pocket. Report of case(s): A 49-year-old male with severe OSA (AHI 30.8/hour) was implanted with a HGNS two years ago with successful activation a month later. He successfully up titrated his amplitude to the maximum stimulation level within his set range (0.9v – 1.7v). He underwent HGNS titration with AHI reduction to 13.9/hour at 2.1 volts and given a new higher range of 1.5 to 2.5 volts. This was accompanied by reduction in snoring, witnessed apneas and associated arousals with more consolidated sleep and improvement in his Epworth sleepiness score to 3 from 12 as noted prior to HGNS. The patient continued to up titrate over the next six months within his new range to 2.4 volts, when he reported increased sensitivity and intolerance at every stimulation level with recurrence of snoring and daytime sleepiness. He underwent interrogation of his device with subsequent awake endoscopy and change to his electrode configuration with a new lower range of 1.0 to 2.0 volts. However, he continued to have the same complaints. A second interrogation revealed increased impedance within the circuit of the respiratory sensing lead which was reproducible. The patient underwent sensing lead replacement in the operating room. He has since been able to increase stimulation levels without complaints and improvement in his OSA symptoms and is scheduled to have a follow-up hone sleep test (HST). Conclusion: This case illustrates the importance of a structured approach in the evaluation of a reduced tolerance to HGNS. This includes assessing adherence, interrogation of the device's circuitry, evaluating electrode configurations, stimulation thresholds with consideration for awake endoscopy. Repeating this process may be necessary to detect rare or delayed mechanical problems that may occur over time with HGNS. Support (if any):